2011
DOI: 10.2337/dc11-1093
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Architecture and Glucose and Insulin Homeostasis in Obese Adolescents

Abstract: OBJECTIVESleep deprivation is associated with increased risk of adult type 2 diabetes mellitus (T2DM). It is uncertain whether sleep deprivation and/or altered sleep architecture affects glycemic regulation or insulin sensitivity or secretion. We hypothesized that in obese adolescents, sleep disturbances would associate with altered glucose and insulin homeostasis.RESEARCH DESIGN AND METHODSThis cross-sectional observational study of 62 obese adolescents took place at the Clinical and Translational Research Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
3
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 27 publications
6
87
3
7
Order By: Relevance
“…The data indicate that both obesity and sleep fragmentation in OSA are significantly associated with altered metabolic variables, including insulin resistance and lipid profile, whereas the frequency of nocturnal respiratory events or severity of nocturnal hypoxaemia exerts a minor effect, if any. The results of this study reinforce the conclusions of studies that demonstrated a prominent role of obesity [17][18][19][20][21] and sleep structure [22,23] as determinants of alterations in insulin resistance/sensitivity in children with OSA, but are at odds with other studies indicating an independent influence of OSA [24][25][26][27][28][29][30][31].…”
Section: @Erspublicationscontrasting
confidence: 41%
“…The data indicate that both obesity and sleep fragmentation in OSA are significantly associated with altered metabolic variables, including insulin resistance and lipid profile, whereas the frequency of nocturnal respiratory events or severity of nocturnal hypoxaemia exerts a minor effect, if any. The results of this study reinforce the conclusions of studies that demonstrated a prominent role of obesity [17][18][19][20][21] and sleep structure [22,23] as determinants of alterations in insulin resistance/sensitivity in children with OSA, but are at odds with other studies indicating an independent influence of OSA [24][25][26][27][28][29][30][31].…”
Section: @Erspublicationscontrasting
confidence: 41%
“…Максимальная продолжительность ОВС выявлена у пациентов первой группы -6,15 [5,40; 6,43] Оригінальні дослідження /Original Researches/ ция ее мозгом уменьшается. Описанные результаты находят подтверждение в литературе об обратной зависимости между значением НbА1с и продолжи-тельностью медленноволнового сна [12][13][14]. При-веденные результаты свидетельствуют о том, что декомпенсация препятствует углублению стадий сна, поэтому в структуре сна преобладают REM-сон, а также поверхностные стадии медленного сна.…”
Section: результатыunclassified
“…Sleep is crucial in childhood and The focus of attention between sleep and metabolic dysfunction has shifted with more attention now concentrating on sleep architecture. Sleep architecture (sleep staging) in relation to glucose metabolism has been explored in children and adolescents, with an initial focus on those with obesity [28,46]. A recent study investigated the effect of sleep staging upon glucose tolerance, insulin sensitivity and pancreaticcell function in children and adolescents (n = 118; mean age 13.1 years; 45% boys) [82].…”
Section: Sleepmentioning
confidence: 99%